2022
DOI: 10.1088/1361-665x/aca7a4
|View full text |Cite
|
Sign up to set email alerts
|

A novel two degree of freedom single magnet bistable energy harvester based on internal resonance

Abstract: Up to now, many nonlinear techniques such as bistable structure have been used to harvest vibration energy from the environment to achieve a wide response bandwidth. However, most bistable harvesters require two opposing magnets to form the potential energy function, which limits the miniaturization of the harvesters. In this paper, a two-degree-of-freedom U-shaped single magnet bistable energy harvester (SMBEH) based on the internal resonance technique is proposed. The harvester consists of a U-shaped beam, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…The superposition of equations ( 8)-( 11) enables the complete magnetic induction intensity at S (x, y, z) within the magnetic field generated by the two annular magnets to be represented as: (12) According to the magnetizing current method, the magnetizing currents of the two annular magnets generate a magnetic field that induces an ampere force on the magnetizing currents of the rectangular magnet, which can be expressed as [40,41]:…”
Section: The Ph and Its Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The superposition of equations ( 8)-( 11) enables the complete magnetic induction intensity at S (x, y, z) within the magnetic field generated by the two annular magnets to be represented as: (12) According to the magnetizing current method, the magnetizing currents of the two annular magnets generate a magnetic field that induces an ampere force on the magnetizing currents of the rectangular magnet, which can be expressed as [40,41]:…”
Section: The Ph and Its Mathematical Modelmentioning
confidence: 99%
“…Energy harvesters are designed to address these limitations by collecting renewable energy sources such as thermal energy, rain energy, wind energy, solar energy, and vibration energy from the environment and converting them into electrical energy to power sensors or electronic devices, which not only fulfill the power supply needs of microelectronic devices in certain specialized environments but also offer environmental sustainability and pollutionfree energy generation [8][9][10]. Among various renewable energy sources, vibration energy is widely prevalent in industrial and daily life activities, including machinery operation, transportation, and human movement [11,12]. Therefore, researchers have shown substantial interest in vibration energy harvesters [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Among these sources, mechanical vibration is widely distributed in human motions, transport systems, electronic devices and so on [21]. Hence, mechanical energy harvesters have drawn great interests recently [22][23][24][25]. The piezoelectric energy harvester, which is based on the direct piezoelectric effect of piezoelectric materials, is one of the common mechanical energy harvesters, and it is widely investigated by lots of researchers owing to its high energy conversion efficiency [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al (2022b) presented an internal resonance piezoelectric energy harvester with three-dimensional coupled bending and torsional modes and shown that the fine-tuned system leverages a two-to-one internal resonance between its first torsion and second bending modes to enhance the power output. Huang et al (2023) designed a TDOF U-shaped single magnet bistable energy harvester based on the internal resonance technique and demonstrated the proposed system can produce a significant output in two frequency ranges. Xu and Zhao (2022) introduced a novel TDOF galloping energy harvester with 2:1 internal resonance for efficient dual-source energy harvesting, and obtained that at the wind speed of 3 m / s and base acceleration of 0 . 9 m / s 2 , the proposed scheme achieves a 211 . 1 % increase in the effective bandwidth and a 50 % increase in the peak voltage around the first resonance.…”
Section: Introductionmentioning
confidence: 99%